Stress analysis on large-diameter buried gas pipelines under catastrophic landslides - Sheng-Zhu Zhang (KeAi Communications Co., Ltd., 2017)
Abstract This paper presents a method for analysis of stress and strain of gas pipelines under the effect of horizontal catastrophic landslides. A soil spring model was used to analyze the nonlinear characteristics concerning the mutual effects between the pipeline and the soil. The Ramberg–Osgood model was used to describe the constitutive relations of pipeline materials. This paper also constructed a finite element analysis model using ABAQUS finite element software and studied the distribution of the maximum stress and strain of the pipeline and the axial stress and strain along the pipeline by referencing some typical accident cases. The calculation results indicated that the maximum stress and strain increased gradually with the displacement of landslide. The limit values of pipeline axial stress strain appeared at the junction of the landslide area and non-landslide area. The stress failure criterion was relatively more conservative than the strain failure criterion. The research results of this paper may be used as a technical reference concerning the design and safety management of large-diameter gas pipelines under the effects of catastrophic landslides.